No Traces of SARS-CoV-2 In Wounds of COVID-19 Positive Patients: A Pilot Study - Gaba, Sunil; Kampalli, Gowtham; Goyal, Kapil; Suri, Vikas; Chauhan, Poonam; Meena, Shyam C.; Bhatnagar, Ankur; Singh, Mini P.; Sharma, Ramesh K. (Indian Journal of Plastic Surgery, 2020)
Background This study was performed to investigate the presence of SARS-CoV-2 virus in wounds of COVID-19 positive patients.Methods This is a single-center observational study. COVID-19 patients with wounds (traumatic/infective/surgical) were included in this study. Preoperative, intraoperative, or postoperative specimens were collected and analyzed with real-time reverse transcriptase polymerase chain reaction (rRT-PCR) to know the presence of the virus.Results A total of eight patients were included in this study. Eleven samples were collected (seven wound swabs, two peritoneal fluids, and two tissue specimens) and analyzed. None of the samples from the wound tested positive for the virus while they were tested positive for nasal swab taken simultaneously or within 3 days prior.Conclusion The wounds of COVID-19 patients are considered negative and can be managed with routine wound precautions.
Keywords: COVID-19; rRT-PCR; wound swab; SARS-Cov-2 virus